HEALTHY LIFE AWARENESS IMPROVEMENT THROUGH HANDWASH HEALTH PROMOTION IN THE KEBONSARI ELEMENTARY SCHOOL, CANDI SUB-DISTRICT, SIDOARJO DISTRICT, EAST JAVA PROVINCE - Faida Annisa; Muhebbi Muhebbi; Ria Devi; Chyntia Tanzila; Bagus Eka Windarta; Nor Aslina; Nora Aditya; Nadia Putri (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
An increase in awareness of healthy living through health promotion in the Kebonsari Elementary School, Candi Sub-District, Sidoarjo District, East Java Province is a form of education in the form of counseling aimed at fostering and improving healthy behavior in children early, especially in carrying out clean and healthy behaviors (PHBS) with 6-step hand washing. The activity was held on December 12, 2017 at Kebonsari Elementary School, Kebonsari Village, Candi District, Sidoarjo Regency, East Java Province. With the aim is fourth grade students at Kebonsari Elementary School, Kebonsari Village, Candi Sub-District, Sidoarjo District, East Java Province. Before the implementation of the activity, there is a process of preparing activities for 3 weeks before the activities are carried out, starting from the selection of health counseling materials to the submission of permits to related parties. As an evaluation, the activity was attended by 52 female students and 1 teacher, participants participated in the activity enthusiastically and conductively, the activities could be carried out on time smoothly. Keywords: Handwash health promotion, healthy life awareness, elementary school, 6-step hand washing.